TRIAS POLITICA: CONSIDERING THE IMPACT OF THE ABSENCE OF THE TRIAS POLITICA IN A COUNTRY - Ali Shofiyah Maskur, Afif; Satria Adam Aryanto, Zaky; Vairuz Zamzami, Muhammad; Indrasta, Farel (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2024)
The Trias Politica, a concept first introduced by Montesquieu in The Spirit of Laws (1748), is an important foundation for modern democratic systems of government. The separation of powers into three main branches-legislative, executive, and judicial-aims to prevent the concentration of power that could lead to abuse of authority. However, the absence of an effective Trias Politica can have a significant impact on political stability, public trust, and government accountability. This research uses a descriptive qualitative approach to analyze the phenomenon of the absence of the Trias Politica in the global and national contexts. The results show that the non-optimal implementation of the Trias Politica, such as in Indonesia, creates major challenges, including weak legislative oversight, compromised judicial independence, and executive policies that are not in favor of the people. Reforms to the system of government are needed to ensure an effective balance of power and guarantee justice and political stability.